Microsoft 365 Identity and Services Exam Guide MS-100 Expert Tips and Techniques to Pass the MS-100 Exam on the First Attempt. - Guilmette, Aaron (Packt Publishing, Limited, 2023)
Gain a comprehensive grasp on the key objectives to pass the MS-100 exam, reinforced with practice questions throughout the book Purchase of the print or Kindle book includes a free PDF eBook Key Features Plan and implement Azure AD identity, including your choice of authentication strategy and securing access Configure core features such as self-service password reset and Azure AD identity protection Work with self-assessment questions, exam tips, and practice tests based on the latest exam blueprint Book Description This book serves as a comprehensive guide to prepare you for the Microsoft Identity and Services exam, which focuses on the core identity and security aspects of a Microsoft 365 tenant. The exam MS-100 tests your proficiency in Azure AD authentication types, user management roles, access management, and workload applications. This book follows the published MS-100 blueprint, which covers identity and identity synchronization concepts, administrative roles, and crucial security topics such as self-service password reset, Azure AD password protection, and multifactor authentication. You'll gain insights into application and authentication concepts, including OAuth application request management, enterprise application configuration, the benefits of Azure AD Application Proxy, and deploying Microsoft 365 apps. The book also delves into passwordless sign-in methods and provides overviews of configuring Exchange Online, Microsoft Teams, SharePoint Online, and OneDrive for Business in both cloud-only and hybrid deployments. You'll be able to assess your knowledge retention at the end of each chapter. By the end of this MS-100 study guide, you'll have built the knowledge and skills to pass the MS-100 exam and be able to ensure thorough preparation with the help of practice exam questions. What you will learn Build your knowledge to effectively plan a Microsoft 365 tenant Examine and monitor health metrics in the Microsoft 365 environment Select an authentication model that aligns with both business and security requirements Implement App Proxy, enterprise applications, and SAML integration Configure Exchange Online and Exchange hybrid scenarios Deploy the Microsoft 365 Apps seamlessly in your organization Explore the core features of SharePoint Online, OneDrive, and Teams Who this book is for Designed for both intermediate and experienced administrators, as well as individuals preparing to take the MS-100 exam, this book caters to those pursuing standalone achievement or aspiring to attain the Microsoft 365 Certified: Enterprise Administrator Expert certification. A foundational understanding of Microsoft 365 services and associated technologies is expected.